Study of Law and Democracy on Lex Semper Dabit Remedium During the Pandemic 2020 in Banten Province - Septia Salikhah Utami; Bambang Herlambang Irawan Nurraid; Citraresmi Widoretno Putri (East Asian Journal of Multidisciplinary Research, 2022)
During the Pandemic Period 2020, there are 48 countries that postponed or continued general elections. In Indonesia during the 2020 pandemic, the concern is regarding the post-conflict local election considering the right time to be able to implement democracy while still taking precautions against the Covid 19 pandemic. So the author is concerned with reviewing Law and Democracy in 2020 As Lex Semper Dabit Remedium during the Pandemic Period in Banten Province. With the law as lex semper dabit remidium, namely where the law will always give medicine in democratic activities during the pandemic, democratic activities by rearranging their schedules in several countries including Indonesia can still be carried out but by using health protocols to prevent the transmission of the covid 19 virus.